Place as layered and segmentary commodity: place branding, smart growth and the creation of product and value. Issue 2 (2nd April 2016) - Van Assche, Kristof; Beunen, Raoul; Lo, Ming Chien
ABSTRACT: Smart growth is a comprehensive version of spatial planning that can guide sustainable development and tackle negative social and environmental consequences of urbanization. In this paper we explore how an integration of spatial planning and place branding strategies can further the concept of smart growth and improve its chance at implementation. A review of the parallel evolutions of place branding and smart growth shows their shared interest in comprehensive visions, sensitivity for narratives of place and self, and the proposed embedding in participatory governance. The concept of layered and segmenatary commodification offers a novel perspective on value creation in smart growth and helps to develop new forms of smart growth, that combine and integrate elements of spatial planning and place branding.